Anthropogenic Iodine‐129 Traces Complex Inflows of Atlantic and Pacific Waters Into the Western Arctic - Yuanzhi Qi; Xinru Xu; Qiuyu Yang; Takeyasu Yamagata; Hiroyuki Matsuzaki; Hisao Nagai; Yuichiro Kumamoto (Geophysical Research Letters)
Abstract Changes in Atlantic and Pacific inflows into the Arctic are contributing to Arctic warming and reshaping water circulation. However, knowledge gaps remain regarding circulation pathways in the western Arctic Ocean, where Arctic Atlantic Water (AAW) and Pacific Water interact. Here, we report iodine‐129 (129I) concentrations in seawater collected from the western Arctic Ocean and Bering Sea in 2021. The wide range of 129I concentrations (1–355 × 107 atoms/L) highlights its value as a tracer for identifying water masses and deciphering circulation patterns. Depth profiles of 129I reveal that AAW enters the western Arctic via multiple pathways, with the top layer potentially diverging from the boundary flow and dispersing throughout the region. This previously unreported feature suggests a broader AAW influence on the western Arctic. Additionally, 129I concentrations provide direct evidence that the cold halocline effectively limits the upward transfer of matter from AAW to the Arctic surface.